Beer, Wood, and Welfare - Michael Grimm; Jörg Peters (Institute for the Study of Labor (IZA), 2014)
Local beer breweries in Burkina Faso absorb a considerable amount of urban woodfuel demand. We assess the woodfuel savings caused by the adoption of improved brewing stoves by these, mostly female owned, small enterprises and estimate the implied welfare effects through the woodfuel market on private households. We find substantial wood savings among the breweries and, subsequently, huge welfare gains for households. Since woodfuel is predominantly used for cooking by the poorer strata, the intervention under study is an example for a green growth intervention with pro-poor welfare gains something green growth strategies should look for.
Keywords: D2; D6; I3; O3; 330; demand for woodfuel; technology adoption; improved stoves; green growth; impact evaluation; female employment